Pengaruh Beberapa Konsentrasi Larutan Chrysal terhadap Vase Life Bunga Potong Hortensia (Hydrangea macrophylla) - VERINA, JEYANTHI; ASTAWA, I NYOMAN GEDE; SUKEWIJAYA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.12, No.1, Januari 2023, 2023)
Effect of Several Concentrations of Chrysal Solution on Vase Life of Cut Hydrangea Flowers (Hydrangea macrophylla) Hydrangea or hydrangea flowers has a unique color and shape of flower buds. However, like other horticultural products, cut flowers have a relatively short vase life (perishable). The decrease in the quality of cut flowers after postharvest is caused by the ongoing respiration process. For the quality of cut flowers to remain fresh for a relatively long time, cut flowers need to be given post-harvest handling so that the quality of cut flowers remains good, which is by using a preservative solution. In short, preservative solutions generally contain sugar, germicide, and citric acid which can help prolong vase life. This study aims to determine the effect of chrysal solution in prolonging the vase life of hydrangea flowers and to determine the best concentration of preservative solution to maintain the vase life of hydrangea flowers (Hydrangea macrophylla). The study used a single factor completely randomized design (CRD) in the form of Chrysal preservative solution with concentrations of 0 ppm (C0), 5000 ppm (C1), 7500 ppm (C2), 10000 ppm (C3), and 12500 ppm (C4). The results showed that the best concentration of Chrysal obtained was with a concentration of 10000 ppm chrysal solution with a long vase life of 11.20 days.